The place of dabigatran in the treatment of patients with atrial fibrillation in the light of modern recommendations - E. S. Kropacheva; E. P. Panchenko (Атеротромбоз)
This review is devoted to the aspects of anticoagulant therapy in patients with atrial fibrillation in the light of the modern understanding of this type of arrhythmia as a polymorbid continuously developing syndrome. According to experts, the management strategy of this category of patients is based on an integrated assessment, including the risk of stroke, the presence of symptoms, assessment of structural heart disease and mandatory accounting of concomitant pathology. In this approach, the appointment of anticoagulant therapy as a prevention of stroke in a patient with atrial fibrillation is put in the first place. At the same time, experts emphasize the need for a dynamic reassessment of risks, as well as the use of a multidisciplinary team of specialists to make a complex decision. The review summarizes the basic concepts of the integrated approach, describes various variants of clinical scenarios, including aspects of anticoagulant maintenance of cardioversion and catheter ablation, multicomponent therapy after percutaneous coronary intervention. A separate chapter is devoted to modern algorithms of perioperative management of a patient receiving oral anticoagulants, which is based on the stratification of interventions according to the risk of perioperative bleeding and the characteristics of the anticoagulant prescribed to the patient. The place of dabigatran in the primary and secondary prevention of stroke and systemic embolism in patients with atrial fibrillation is described, studies that served as the basis of the evidence base for the use of dabigatran in patients with atrial fibrillation are presented. The data of register observations, meta-analyses devoted to the evaluation of the efficacy and safety of dabigatran in certain categories of patients (elderly patients, patients with chronic heart failure, diabetes mellitus) are presented, which form the basis of decision-making in real clinical practice.